2016
DOI: 10.1371/journal.pone.0149742
|View full text |Cite
|
Sign up to set email alerts
|

The Transmission and Antibiotic Resistance Variation in a Multiple Drug Resistance Clade of Vibrio cholerae Circulating in Multiple Countries in Asia

Abstract: Vibrio cholerae has caused massive outbreaks and even trans-continental epidemics. In 2008 and 2010, at least 3 remarkable cholera outbreaks occurred in Hainan, Anhui and Jiangsu provinces of China. To address the possible transmissions and the relationships to the 7th pandemic strains of those 3 outbreaks, we sequenced the whole genomes of the outbreak isolates and compared with the global isolates from the 7th pandemic. The three outbreaks in this study were caused by a cluster of V. cholerae in clade 3.B wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
(47 reference statements)
1
10
0
1
Order By: Relevance
“…This result indicated that early wave 3 has remained in Bangladesh. In comparison, the isolates in the recent catastrophic outbreaks in Yemen and Haiti were related to lineage 2, and several reports demonstrated that the source of spreading was derived from India (12,19), whereas lineage 1 has been associated with epidemics in China and Vietnam (27,31). The factor(s) causing the difference in epidemic scale was unclear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result indicated that early wave 3 has remained in Bangladesh. In comparison, the isolates in the recent catastrophic outbreaks in Yemen and Haiti were related to lineage 2, and several reports demonstrated that the source of spreading was derived from India (12,19), whereas lineage 1 has been associated with epidemics in China and Vietnam (27,31). The factor(s) causing the difference in epidemic scale was unclear.…”
Section: Discussionmentioning
confidence: 97%
“… V. cholerae was isolated by streaking the stool samples on thiosulfate citrate bile salts sucrose (TCBS) agar plates, and typical sucrose-fermenting yellow colonies were considered presumptive V. cholerae . Single isolated yellow colonies were streaked on an LB agar plate (Difco), and then the bacterial lawn on the LB agar plate was subjected to an oxidase and string test as described earlier ( 31 ). Oxidase and string test-positive cultures were checked for slide agglutination to confirm their serogroup with polyvalent O1-specific antisera according to the manufacturer’s instruction (Denka Seiken).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other clinical strains exhibited resistance to TET, AZM, and AMP in contrast to the environmental strains which were mostly resistant to NAL followed by AMP, TMP, and TET. Previous reports have described different antimicrobial resistant profiles compared with those from Thailand, such as resistance to furazolidone, NAL, sulfisoxazole, streptomycin, and trimethoprim/sulfamethoxazole in Haiti [56] as well as TET, streptomycin, sulfisoxazole and trimethoprim in China [57]. During 2003–2011, V .…”
Section: Discussionmentioning
confidence: 99%
“…19,26 Recentemente várias investigações abordaram e apontaram um problema real de resistência de V. cholerae O1 à tetraciclina e outros antimicrobianos em diversas áreas, predominantemente na África e Ásia. 27,28 Dessa forma, os antibióticos encurtam o curso e diminuem a gravidade da doença, mas não são tão importantes quanto a reidratação.…”
Section: Tratamento Vigilância E Recursos Em Saúdeunclassified